2007
DOI: 10.1080/08923970701675101
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Co-stimulatory Molecules on Langerhans Cells in Lesional Epidermis of Human Atopic Dermatitis

Abstract: Langerhans cells (LC) are immature dendritic cells (DC) present in the skin epithelium. To understand the molecular and cellular mechanisms governing the inflammatory reaction in atopic dermatitis (AD), the expression of the LC specific marker CD1a, a member of major histocompatibility (MHC)-like glycoproteins, and the co-stimulatory molecules CD80 and CD86, expressed on functionally mature dendritic cells, were counted in lesional biopsies and normal epidermis by an immunohistochemical method. CD1a specific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The NAB2 , which also interacts with the transmembrane protein KIAA0286 in our asthma model, has been shown to modulate the vascular endothelial growth factor ( VEGF ) pathway. We and others have previously shown that the VEGF pathway is implicated in asthma pathogenesis and airway remodeling that occurs in persistent asthmatics (28). These gene relationships, which could not be identified by our single‐SNP analysis, are interesting biologic candidates for follow‐up investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The NAB2 , which also interacts with the transmembrane protein KIAA0286 in our asthma model, has been shown to modulate the vascular endothelial growth factor ( VEGF ) pathway. We and others have previously shown that the VEGF pathway is implicated in asthma pathogenesis and airway remodeling that occurs in persistent asthmatics (28). These gene relationships, which could not be identified by our single‐SNP analysis, are interesting biologic candidates for follow‐up investigation.…”
Section: Discussionmentioning
confidence: 99%
“…They bind with corresponding receptor or ligand on T cells surface, which serves as the second signal for T cell activation. Recent study reported that the CD80/CD86 mediated signal determines the polarization of the T cell differentiation towards either Th1 or Th2 [24]. In our in vitro experiments, we showed that VIP significantly up-regulated the expression of CD80, CD86, CD40, CD54 in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 54%